Analisis Inovasi Produk, Orientasi Pasar dan Strategi Bersaing dalam Meningkatkan Kinerja Bisnis Coffee Shop Survei pada Coffee Shop di Kota Sukabumi - aljaidi, salha said; Sunarya, Erry; Ramdan, Asep Muhamad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The growth of Coffee shops in Sukabumi City can be said to be high for a small city, there are already 54 Coffee shops which previously only had 37 Coffee shops. This indicates the high growth of Coffee shops in Sukabumi City. However, it also indicates the tight competition of Coffee shops in Sukabumi City. This researcher aims to determine how much influence product innovation, market orientation and competitive strategy have in improving business performance in coffee shops. This researcher uses descriptive and associative methods with a quantitative approach. The population in this study was coffee shops in Sukabumi City as many as 54 coffee shops. The data analysis techniques used in this study are the classical assumption test, multiple correlation coefficient, determination coefficient, multiple linear regression, and simultaneous hypothesis testing (F Test) and partially (T Test). The results of this study indicate that product innovation, market orientation and competitive strategy have a significant effect on business performance, this is evidenced by the calculated F 80.307> F table 2.790 which means the calculated F value is greater than the F table. Partially, product innovation has a significant effect on business performance, this is evidenced by the T count of 8.485> T table 1.674, which means that T count is greater than T table. Market orientation has a significant effect on business performance, this is evidenced by the T count of 2.604> T table 1.674, which means that T count is greater than T table. Then the competitive strategy does not have a significant effect, this is evidenced by the T count of 0.220> T table 1.674, which means that T count is smaller than T table with an error level of 0.05.